Semantics typology, diachrony and processing - Heusinger, Klaus von; Maienborn, Claudia; Portner, Paul (Mouton reader., 2019)
"Now available in paperback for the first time since its original publication, the material in this book provides a broad, accessible guide to semantic typology, crosslinguistic semantics and diachronic semantics. Coming from a world-leading team of authors, the book also deals with the concept of meaning in psycholinguistics and neurolinguistics, and the understanding of semantics in computer science. It is packed with highly cited, expert guidance on the key topics in the field, making it a bookshelf essential for linguists, cognitive scientists, philosophers, and computer scientists working on natural language"--